Model Kolaborasi Program Untuk Meningkatkan Kesehatan Suku Anak Dalam Jambi - Ridwan, M.; Noerjoedianto, Dwi; Kalsum, Ummi; Ningsih, Vinna Rahayu (Jurnal Kesmas Jambi, 2024)
The long journey of the Indigenous Children program in Jambi has been carried out. The success of the program has not yet been widely felt by the indigenous community. The aim of this research is to delve deeper into the collaborative work carried out in the SAD group of Bungo Regency. This research method uses a qualitative design with a case study design. Informants are selected according to purposive sampling. Data collection was conducted through in-depth interviews, observations, and FGDs. The research informants numbered 27 people, and data collection was assisted by 3 enumerators from the Anak Dalam tribe facilitators to facilitate communication at the research location. Data was analyzed using content analysis. The research in Bungo Regency Result: each sector of the local government has already implemented programs, but none have specifically targeted the indigenous children's community. There has not yet been a synergistic planning of programs among stakeholders. The program that has been worked on has already been reported to Bapeda as the coordinator of programs in the district. There is currently no specific institution that manages the indigenous community programs.  program observations have been completed by each stakeholder, including NGOs, universities, companies, and local governments.  The need for program collaboration and the establishment of a special institution to handle it, so that program planning can be carried out effectively and synergy among each stakeholder can implement the program according to the community's expectations.